Metabolic profiling analysis of berberine, palmatine, jatrorrhizine, coptisine and epiberberine in zebrafish by ultra-high performance liquid chromatography coupled with LTQ Orbitrap mass spectrometer. (5th November 2014) - Li, Yan; Wang, Hongjie; Si, Nan; Ren, Wei; Han, Lingyu; Xin, Shaokun; Zuo, Ran; Wei, Xiaolu; Yang, Jian; Zhao, Haiyu; Bian, Baolin
Abstract: 1. Zebrafish has been used in metabolic study of drugs as a powerful tool in recent years. In this study, we make a feasible metabolism investigation of five protoberberine alkaloids (PBAs) applied in zebrafish model for the first time, including berberine (BBR), palmatine (PAL), jatrorrhizine (JAT), coptisine (COP) and epiberberine (EBBR). 2. After exposure for 24 hours, 19 metabolites were identified by LTQ Orbitrap mass spectrometer, including 9 phase I metabolites and 10 phase II metabolites. Demethylation, hydroxylation, sulfation and glucuronidation were the major metabolic transformation of PBAs in zebrafish, which were similar to mammals. Compared with reported literatures, BBR and JAT showed high consistency between human and zebrafish in metabolic pathways. 3. To our knowledge, this is the first time to study in vivo metabolism of COP, which provides useful information to other researchers. 4. This study indicated that zebrafish model is feasible and reasonable to predict the metabolism of PBAs. It showed great potential for developing a novel and rapid method for predicting the metabolism of trace compounds of botanical drugs, with the advantages of lower cost, higher performance and easier set up.